'Hebrew Tarzans' from Arthur Koestler's Thieves in the Night to Netflix and Fauda. Issue 1 (May 2021) - Salt, Jeremy
Abstract : Core elements of Zionist propaganda justifying the colonisation of Palestine are exploited again in the four books critiqued in this article ( Thieves in the Night; Promise and Fulfilment. Palestine 1917–1949; Exodus ; and The Haj ). For propaganda to be viable, however, it has to be adapted to changing circumstances. Recent Israeli television dramas such as Fauda (Chaos) have realigned images without letting go of the central elements in the propaganda war. In Fauda, Israeli killings in the occupied territories are virtually advertised, as if the state wants viewers to see what it is capable of doing in the name of combatting 'terrorism'.